Nuansa Islami Dalam Novel Surga Yang Tak Dirindukan dan Novel Kehormatan Dibalik Kerudung: Kajian Interteks dan Implementasinya Dalam Pembelajaran Sastra Indonesia di MA - Anam, Nova Khairul, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum, Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
The study has five principal 1) describes the socio-historical background of the author of the novel SyTD and the novel KdBK, 2) describe a study strukturalnovel SyTD and novel KdBK, 3) to describe aspects of Islamic nuances that exist in the novel SyTD and novel KdBK 4) Describe the intertextual relationship between the novel SyTD with novel KdBK, and 5) ImplementnovelSyTDand novel KdBK as material learning teaching language and literature Indonesian in islamic senior high school.This study used descriptive qualitative method. Strategy studies using a case spikes (Embedded Case Study) .Subjek this study is the work of Asma Nadia SyTD novel and novel KdBK work Affany Ma'mun. The object of this research is that there are shades of Islamic religion in the novel using intertextual approach. The data in this study is qualitative data which is a trailer that contained in the novel, through purposive technique Sampling.Data source in this study are two novels are novels SyTD andKdBK.Data collection technique in this study using engineering studies literature, see and record. Validity research data using trianggualasi kredebilitas test, data sources and data collection (observation) investigator in the form of document novels KdBK. Tecnique analysis data using a model of semiotic readings heuristics and hermeneutics. The results produce five dicussion.1) Sosio-historical background of the author shows the different studies and all of them indeed affect his work. 2) Structural analysis shows that equation is on the theme of polygamy in the family realm. Differences looked at all the components that includes plot, character and characterization as well as the background. Flow in the novel SyTD using a mixture of groove, while the novel KdBK using advanced flow. Character and characterization in the novel SyTD there are 7, at the same time novel KdBK figures there are 8. Each character has a character different characterizations in accordance with their respective roles. Background used in novel SyTD and KdBK background includes time, place and social. 3) Islamic atmosphere in the novel KdBK more and feel when compared with SyTD novel. 4) Intertextual relationship shows that previous novel (KdBK) into Hypogram of the latest novel (SyTD) into text transformation. 5) Its implementation is timely as the second novel in accordance with the function of literature and literary learning function.